Stability Mechanism Analysis of Traction Power System and Traction Drive System - Huazhi ZHANG; Jun HUANG; Bo ZHAN; Jie WU; Wensheng SONG (机车电传动)
In view of the frequent occurrence of tripping in a domestic passenger dedicated line traction substation, which brought safety hazards to the normal operation of the power supply system and the high-speed trains. In order to seek the mechanism of the fault and guide the construction of high-speed railway in the future, this paper firstly used the impedance ratio criterion to establish the transfer function model of the closed loop system of the vehicle-grid system, revealed the mechanism of low-frequency oscillation caused by impedance parameter mismatch, and analyzed the low frequency oscillation caused by network voltage-power limit protection of high-speed trains. Then the vehicle-grid system simulation model was built and joint simulation was performed to reproduce the field fault phenomenon based on MATLAB/Simulink software. The theoretical analysis and simulation of this paper validated the two causes of low frequency oscillation, which can provide guidance for the actual field oscillation suppression, and thus ensure the stable and safe operation of the vehicle-grid system.